THE LEGAL STANDING OF ADAT INSTITUTIONS IN DISPUTE RESOLUTION IN ACEH COMMUNITY, INDONESIA - Muslem (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2020)
The implementation of regional autonomy is carried out through regional regulations. Perda is the most important element for local government in order to fulfill the needs of the region. Particularly for the people of Aceh, one of the needs of the community is to carry out customary life and customs which are characteristic of Aceh's distinctiveness in addition to the implementation of Shari'ah Islam. For this reason, Aceh Qanun Number 9 of 2008 was born on the Development of Customs and Customs and Aceh Qanun Number 10 of 2008 concerning Customary Institutions. Acehnese people resolve disputes through Customary Courts which are preserved. Customary justice aims to resolve disputes according to customs and customs in the community itself, even to the implementation of sanctions for customary law. The purpose of customary justice is to solve problems between residents at the village level. However, decisions taken by adat do not have formal legal force. For example, if a husband and wife divorce in an adat court, according to customary law, the couple is officially divorced, but because the law itself does not have formal legal force, then another stage is needed to obtain formal legality. We now hear the term customary justice from MAA circles, and several NGOs that have programs for community empowerment. Whereas in the community itself who practice the mechanism of dispute resolution through customary justice institutions do not say to settle cases through customary justice. The community has its own terms such as pedame ureung (reconcile people), peumat jaroe, (bejabat tangan), meudame (make peace). Customary institutions in Aceh function as a vehicle for community participation in the administration of government, development, community development, and settlement of problems or social matters. The function of Indigenous life is also to carry out and streamline customs and customary law to foster community life.